HUBUNGAN DUKUNGAN KELUARGA DENGAN HARGA DIRI (SELF ESTEEM) PENDERITA TUBERKULOSIS PARU DI WILAYAH EKS KAWEDANAN INDRAMAYU - Dedeh Husnaniyah (JURNAL KESEHATAN INDRA HUSADA, 2017)
Pulmonary tuberculosis is an infectious disease caused by tuberculosis.The Impact of pulmonary tuberculosis is a decrease of body endurance, physical weakness, economically detrimental and can lead to social isolation. Those conditions can affect self-esteem patients with pulmonary Tuberculosis.Changes in self-esteem in patients with pulmonary TB can affect the success of treatment, so, the support of the family is needed.The purpose of this study is to identify the effect of family support for self-esteem of pulmonary tuberculosis patients in the territory of the health center eks Kawedanan Indramayu 2015. The design of the research is an analytic descriptive with cross sectionalapproach.Sampling was done by total sampling technique 45 respondents The results show that patients with pulmonary TB who have high self-esteem are 23 respondents (51.1%) and have low self-esteem are 22 respondents (48.9%), pulmonarytuberculosis patients who receive family support are 26 respondents (57, 8%) and who have no family support are 19 (42.2%).Respondents who receive family support, have more high self-esteem compared to respondents who have no family support, its percentage is 69.6% with p value = 0.047 (<0.05).Conclusion from this research is that there is the corelation of family support for self-esteem of pulmonary tuberculosis patients.The results of the study are expected to be input for holders of TB program to provide counseling about the importance of family support for patients with pulmonary tuberculosis.